Why do people with similar levels of internal control differ in their likelihood to commit fraud? Analysis of the moderating effect of perceived opportunity to commit fraud - Sun, Xiaonan; Chen, Yan (Frontiers in Psychology, 2022)
This research focuses on one of the three components of the fraud triangle, namely opportunity, and empirically tests the tendency to commit fraud. The perceived opportunity to commit fraud can be considered in terms of temptation and obstacles. This research employs concepts from cognitive psychology, i.e., desire and motivation for action, which affect people’s decision-making processes when presented with an opportunity to commit fraud. Questionnaires were used to analyze the tendency to commit fraud. First, dispositional differences among people differing in self-control were observed, which may influence the likelihood of fraudulent behavior. That is, low self-control mediates the relationship between self-regard and fraud tendency. Second, strong relationships of both personal disposition and self-efficacy with the tendency to commit fraud were revealed; high self-efficacy enhances the tendency to commit fraud. This research offers a new psychological perspective on fraud opportunity, and showing for the first time that fraud can be reduced not only by improved internal control and external supervision, as suggested in previous studies, but also by changing people’s perceptions of fraud opportunity, given the fallibility of both internal control and external supervision.